THE EFFECTIVENESS OF HEALTH AND SAFETY PROGRAMMES IN ADDRESSING OCCUPATIONAL DISEASES AND INJURIES AT MANUFACTURING FACILITIES IN IBADAN SOUTHWEST LOCAL GOVERNMENT OF OYO STATE, NIGERIA - ADAGBOR , Pedro Uwadum; ADEBOLA , Abibat Motunrayo; OJEABURU , Bukola Linda; Ukpere, Wilfred; Adekanmbi, Foluso (Annals of Spiru Haret University. Economic Series, 2023)
People now spend many years of their adult lives at jobs where they are exposed to various hazardous chemicals, unsafe acts, and other diseases because of population growth and rapid technological advancements. Occupational diseases and injuries may arise because of risk factors in the workplace. The study examined the effectiveness of health and safety programmes in addressing occupational diseases and injuries at manufacturing in Ibadan South-West Local government of Oyo state, Nigeria. The sample size was 250 respondents selected using simple and multi-stage sampling techniques to cover the forty-eight manufacturing companies in the area. A self-structured questionnaire was employed for data, which were analysed using frequencies, percentages, and chi-square at 0.05 alpha level. It was found that the prevalence rate of occupational diseases in the facility had (x2=81.94, p<0.05), the extent to which occupational health and safety programs was promoted had (x2=71.51, p<0.05), the effectiveness of occupational health and safety programs had (x2=64.94, p<0.05). Based on the findings, health education is a panacea to occupational diseases and injuries in Ibadan South-West Local government of Oyo state, Nigeria. It was therefore recommended that Government should provide regular health training programs to review, promote, and maintain occupational health strategies. Manufacturing companies/facilities should employ adequate qualified health educators to enlighten the workers on the risks associated with occupational diseases and injuries